L’encadrement du système financier québécois - de 1983 à 1993 - Bouchard, Jean-Marie (Assurances, 1994)
In the following speech delivered at a seminar organized by Le Monde juridique, Me Jean-Marie Bouchard, Chief Inspector of Financial Institutions, takes stock of his ten years at the helm of this organization that oversees and controls financial institutions in Québec. He discusses the province's financial system and highlights its major building blocks, including the recasting of the legislative and regulatory framework and the founding of the organization he represents. Mr. Bouchard concludes with an outlook for the future, particularly from a standards point of view, the consolidation of the present system and the question of guidelines for a more flexible and efficient framework for Québec' s financial system.